Eradicating Poverty With Religious Moderation: Realizing Social Justice In Indonesia - Fadhilah, Hanifah Nur; Nida, sofwatun; Irhas Sabililhaq; Raisa Zuhra Salsabila Awaluddin (Moderatio: Jurnal Moderasi Beragama, 2025)
Poverty is a central issue in social development in Indonesia. Religious moderation is expected to be a strategic approach to reducing poverty and realizing social justice. This research aims to explore and elaborate concrete strategies for implementing diverse moderation through qualitative methods and literature studies. The results show that religion has great potential in social and economic development. The implementation of diverse moderation through education plays an important role in instilling the values of tolerance, interfaith dialog, and respect for integrity. This education shapes a young generation that is inclusive and plays an active role in overcoming social inequalities. In addition, the optimization of philanthropic institutions, such as zakat, infaq and sadaqah, must be carried out professionally, transparently and sustainably to ensure equity. The synergy between education based on religious moderation and philanthropic management is expected to alleviate material poverty and create an inclusive and socially just society. Religious moderation becomes the main driver in sustainable economic empowerment, building social harmony, and realizing social justice as a whole.